Efficacy and costs of telehealth for the management of COPD: the PROMETE II trial. Issue 5 (31st May 2018) - Ancochea, Julio; García-Río, Francisco; Vázquez-Espinosa, Emma; Hernando-Sanz, Ascensión; López-Yepes, Luis; Galera-Martínez, Raúl; Peces-Barba, Germán; Pérez-Warnisher, Maria Teresa; Segrelles-Calvo, Gonzalo; Zamarro, Celia; González-Ponce, Pablo; Ramos, M. Inmaculata; et al.
Chronic obstructive pulmonary disease (COPD) is a significant and largely underdiagnosed cause of morbidity and mortality worldwide [1]. More long-term survivors with advanced disease have led to an ageing COPD population profile with an increased level of acute exacerbations, hospitalisations and polymorbidity [2]. In the PROMETE II trial, telehealth did not reduce COPD-related use of health services http://ow.ly/KL7t30jotNb